Mathematics
Виктория
37

1. cot x sec4x = cot x + 2 tan x + tan3x 2. (sin x)(tan x cos x - cot x cos x) = 1 - 2 cos2x 3. 1 + sec2x sin2x = sec2x 4. - tan2x + sec2x = 1

+3
(1) Answers
nikolak

1. cot(x)sec⁴(x) = cot(x) + 2tan(x) + tan(3x)     cot(x)sec⁴(x)            cot(x)sec⁴(x)                    0 = cos⁴(x) + 2cos⁴(x)tan²(x) - cos⁴(x)tan⁴(x)                    0 = cos⁴(x)[1] + cos⁴(x)[2tan²(x)] + cos⁴(x)[tan⁴(x)]                    0 = cos⁴(x)[1 + 2tan²(x) + tan⁴(x)]                    0 = cos⁴(x)[1 + tan²(x) + tan²(x) + tan⁴(4)]                    0 = cos⁴(x)[1(1) + 1(tan²(x)) + tan²(x)(1) + tan²(x)(tan²(x)]                    0 = cos⁴(x)[1(1 + tan²(x)) + tan²(x)(1 + tan²(x))]                    0 = cos⁴(x)(1 + tan²(x))(1 + tan²(x))                    0 = cos⁴(x)(1 + tan²(x))²                    0 = cos⁴(x)        or         0 = (1 + tan²(x))²                 ⁴√0 = ⁴√cos⁴(x)      or      √0 = (√1 + tan²(x))²                    0 = cos(x)         or         0 = 1 + tan²(x)          cos⁻¹(0) = cos⁻¹(cos(x))    or   -1 = tan²(x)                  90 = x           or            √-1 = √tan²(x)                                                          i = tan(x)                                                       (No Solution) 2. sin(x)[tan(x)cos(x) - cot(x)cos(x)] = 1 - 2cos²(x)               sin(x)[sin(x) - cos(x)cot(x)] = 1 - cos²(x) - cos²(x)    sin(x)[sin(x)] - sin(x)[cos(x)cot(x)] = sin²(x) - cos²(x)                                sin²(x) - cos²(x) = sin²(x) - cos²(x)                                          + cos²(x)              + cos²(x)                                              sin²(x) = sin²(x)                                            - sin²(x)  - sin²(x)                                                      0 = 0 3. 1 + sec²(x)sin²(x) = sec²(x)            sec²(x)             sec²(x)       cos²(x) + sin²(x) = 1                     cos²(x) = 1 - sin²(x)                   √cos²(x) = √(1 - sin²(x))                      cos(x) = √(1 - sin²(x))                cos⁻¹(cos(x)) = cos⁻¹(√1 - sin²(x))                                  x = 0 4. -tan²(x) + sec²(x) = 1                -1               -1       tan²(x) - sec²(x) = -1                     tan²(x) = -1 + sec²                   √tan²(x) = √(-1 + sec²(x))                      tan(x) = √(-1 + sec²(x))             tan⁻¹(tan(x)) = tan⁻¹(√(-1 + sec²(x))                              x = 0

Add answer